(untitled) (International journal of artificial intelligence, 2026)
This article examines the segmental and supеrsegmental characteristics of spoken language as key components of oral communication. It analyzes the fundamental phonetic processes, their interrelationships, and their impact on speech perception. Particular attention is paid to the role of intonation, rhythm, and stress in spontaneous speech, as well as their interaction with segmental units. A comparative analysis of phonetic phenomena characteristic of spoken language is provided.